(untitled) (Research, Society and Development, 2021)
The capillarity of short agrifood chains enables the generation of economic benefits for both producers and consumers. Therefore, this research aims to investigate the capillarity of the short agrifood chains, established at the family farming fair in the city of Porto Grande - AP and the bottlenecks of this process in the view of marketers. The methodology consists of a descriptive, qualitative research that used the observation technique, having as a universe the open-air market held in the city of Porto Grande – AP. The results indicated that the capillarity of the Short Agrifood Chains in the studied region involves the articulation of attributes and values that are associated with the marketed product and the subjects participating in the transaction. The study also pointed out contributions to improve the structure of the open market in the municipality, aiming to transmit better information to the consumer, as well as identifying the main bottlenecks pointed out by the marketers.